La protección de la selva amazónica por parte de Brasil desde el 2004 hasta la actualidad - Urrea Chávez, Bárbara Alexandra. (2017)
The current global context is characterized by the increasing threats to the development of human life; one of these is the deterioration of the environment, an essential element for all living beings on the planet. It is for this reason that the protection of biodiverse areas has become the focus of government agenda. Brazil, at the South American level, has undertaken actions in order to defend the Amazon Rainforest, since it has about 80% of this ecosystem in its territory. The following research aims to analyze the reasons why the Brazilian government decided to protect this region by incorporating it into its National Defense Policy, as well as cooperate with other countries in South America for the same purpose. Being the subjects of national security and international cooperation, the Realist and Liberal theories of International Relations are the most adapted to the question to be addressed. Thus, the different instruments of foreign policy of the Federal Republic of Brazil will be studied, such as: its National Defense Policy, the National Defense White Paper, and cooperation such as the Amazon Cooperation Treaty Organization. The research leaves Brazil aware of the resources of this biodiverse area, and how important it is for the International System in terms of combating climate change and exploiting unique resources in the world; in addition to preventing illegal deforestation and other activities that damage the Amazon and its conservation. The Brazilian government admits that the International System is anarchic and that many times to protect something that is part of its national interests, it must act in a united way with other nations and thus reach its purpose more quickly than to protect the Amazon Rainforest